Students' View of Causes, Forms and Solutions of Lecturers' Involvement in Corrupt Practices in Tertiary Educational Institutions, Kwara State Nigeria - Rasheed, Shofiu Adewuyi (Universitas Majalengka, 2023)
This descriptive survey investigated students' views on lecturers' engagement in corrupt practices within Kwara State's tertiary educational institutions in Nigeria. The study targeted NCE. Three-level students, with 150 respondents randomly sampled using stratified and purposive techniques from public Colleges of Education. A researcher-designed questionnaire was used, addressing four research questions. Mean and standard deviation analyzed the data, revealing a high level of lecturer involvement in Corruption. Causes cited included greed, students' disinterest in learning, weak enforcement of anti-corruption laws, and lecturer intimidation. Corrupt practices identified encompassed money extortion from students, sexual harassment, score manipulation, forcing `handout purchases, and certificate forgery. Proposed solutions included timely salary payments, robust anti-corruption groups, funding lecturers' international conferences, strict sanctions against wrongdoers, and merit-based recruitment and promotion. These findings emphasize the need to combat Corruption, preserve institutional integrity, and create a conducive learning atmosphere. Implementation of effective anti-corruption measures can promote ethical academic conduct, ensuring transparent and accountable educational systems. Further research and practical interventions are vital to curb Corruption's impact on Nigeria's educational sector.